Clarification of the molecular pathway of Taiwan local pomegranate fruit juice underlying the inhibition of urinary bladder urothelial carcinoma cell by proteomics strategy. Issue 1 (December 2016) - Wu, Ting-Feng; Hsu, Li-Ting; Tsang, Bo-Xian; Huang, Li-Chien; Shih, Wan-Yin; Chen, Li-Yi
Abstract Background Pomegranate fruit has been shown to exhibit the inhibitory activity against prostate cancer and lung cancer in vitro and in vivo, which might be a resource for chemoprevention and chemotherapy of cancer. Our previous documented findings indicated that treatment of urinary bladder urothelial carcinoma cell with the ethanol extract isolated from the juice of pomegranate fruit grown in Taiwan could inhibit tumor cell. In this study we intended to uncover the molecular pathway underlying anti-cancer efficacy of Taiwan pomegranate fruit juice against urinary bladder urothelial carcinoma. Methods We exploited two-dimensional gel electrophoresis coupled with tandem mass spectrometry to find the de-regulated proteins. Western immunoblotting was used to confirm the results collected from proteomics study. Results Comparative proteomics indicated that 20 proteins were differentially expressed in ethanol extract-treated T24 cells with 19 up-regulated and 1 down-regulated proteins. These de-regulated proteins were involved in apoptosis, cytoskeleton regulation, cell proliferation, proteasome activity and aerobic glycolysis. Further studies on signaling pathway demonstrated that ethanol extract treatment might inhibit urinary bladder urothelial carcinoma cell proliferation through restriction of PTEN/AKT/mTORC1 pathway via profilin 1 up-regulation. It also might evoke cell apoptosis through Diablo over-expression. Conclusions The results of this study provide a global picture to further investigate the anticancer molecular mechanism of pomegranate fruit.